KARAKTERISASI FRAKSI TERAKTIF SENYAWA ANTIBIOTIK ISOLAT KP 13 DENGAN METODE DENSITOMETRI DAN KLT-SEMPROT - Alfian Syarifuddin; Nanik Sulistyani (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2019)
Exploration of microorganisms Actinomycetes can produce antibiotic compounds. One of the bacteria that can produce antibiotic compounds is the KP13 bacterial isolate. The purpose of this study was to determine the character of the fraction of KP13 isolates using the densitometry method and the spray / colouring reaction of thin layer chromatography elution. The wavelengths used for densitometry 210 nm and spray reagents used include ninhydrin, Dragendorff, 2,4-dinitrophenyl hydrazine (2,4-DNPH), and sulfuric acid anisaldehyde. The results of the study using densitometry at a wavelength of 210 nm showed the highest peak chromatogram at Rf 0.78. The compound that is thought to be responsible for the Rf value of 0.78 has the characteristics of Terpenoid compounds, alkaloids, and carbonyl.